Social determinants of health: critical consciousness as the core to collective impact - Doll, Joy; Malloy, Julie; Gonzales, Roger (Frontiers in Research Metrics and Analytics, 2023)
Social determinants of health have become widely recognized as important to overall health. Many areas of social determinants of health are growing from policy to reimbursement to the connecting of health and social care. The efforts around social determinants of health require reflection and awareness of structural issues. The work of Paulo Freire in critical consciousness provides guidance for how to engage in social determinants of health efforts. This manuscript offers a summary of the social determinants of health under the guidance of critical consciousness to build skills and interactions to promote social care to build toward health equity.